Clinical aspects of pathogenetic influences defining the immune response in patients with urgent surgical pathology - P. V. Sarap; Yu. S. Vinnik; A. A. Ostanin (Бюллетень сибирской медицины)
Using methods of factorial analysis the values of the main components (MC) defining a condition of various links of immune system in patients with urgent surgical pathology are calculated. MC interrelations with clinical characteristics describe qualitative structure of the factors influencing the organization of immune system indicators. Results of research can be used for forecasting of diseases current and a choice of effective tactics of treatment.